Zolpidem and Gender: Are Women Really At Risk?. Issue 3 (May 2019) - Greenblatt, David J.; Harmatz, Jerold S.; Roth, Thomas
Abstract: Background: In 2013 the Food and Drug Administration (FDA) claimed the existence of new data showing women to be at risk for excessive daytime sedation and impaired driving proficiency following bedtime doses of zolpidem. The putative explanation was the reduced metabolic clearance of zolpidem and higher morning blood concentrations in women compared to men. The FDA acted to reduce the recommended dosage for women down to 50% of the dose for men. No other regulatory agency worldwide has taken similar action. Methods: Gender effects on zolpidem pharmacokinetics, pharmacodynamics, adverse effects, clinical efficacy, and driving performance were evaluated through a further analysis of data from a previous study, together with a literature review. Results: Women had on average 35% lower apparent clearance of zolpidem than men (236 vs 364 mL/min, P < 0.001). This difference was not explained by body weight. In some laboratory studies, women had greater functional impairment than men taking the same dose, but in all studies active drug was not distinguishable from placebo at 8 hours after oral dosage. On-the-road driving studies likewise showed no evidence of driving impairment in men or women at 8 hours after 10 mg of oral immediate-release zolpidem. No clinical trial demonstrated a gender-related difference in clinical efficacy or adverse reactions, and there was no evidence of a particular risk to women. Conclusions: Dosage reduction in women is not supported by available scientific evidence, and may in fact lead to underdosing and the consequent hazard of inadequately treated insomnia.